Perceived Work Conditions and Turnover Intentions: The Mediating Role of Meaning of Work - Arnoux-Nicolas, Caroline; Sovet, Laurent; Lhotellier, Lin; Di Fabio, Annamaria; Bernaud, Jean-Luc (Frontiers in Psychology, 2016)
Perceived working conditions lead to various negative outcomes for employee behaviors, including turnover intentions. Although potential mediators for these relationships were previously identified, the importance of meaning of work has not yet been investigated. This study examines the role of this psychological resource as a mediator for the relationships between perceived working conditions and turnover intentions in a sample of 336 French workers from different job contexts. Results show that adverse working conditions were positively and significantly associated with turnover intentions. Meaning of work is negatively related to both perceived working conditions and turnover intentions. Mediation analyses for meaning of work demonstrated indirect effects of several adverse working conditions on turnover intentions. The role of meaning of work as a psychological resource for employees facing adverse working conditions is discussed, especially regarding its implications for research and practice within organizational contexts.